Function of tumor suppressor genes in head and neck cancer - Szukała, Katarzyna; Szyfter, Krzysztof; Kujawski, Maciej (Contemporary Oncology/Współczesna Onkologia, 2003)
The first goal of tumor biology is to gain knowledge on mechanisms of carcinogenesis and oncogenesis and only then to pass it to a clinical practice. The two-hit hypothesis proposed by A. Knudson has stimulated intensive studies on oncogenes and tumor suppressor genes (TSG) and their role in oncogenesis. A discovery of numerous TSG has resulted in their functional classification. A significance of TSG is associated with their inhibitory role in neoplastic transformation, starting from blocking uncontrolled proliferation of an initiated cell. The cytogenetic and molecular studies have shown that the significance of TSG defects is not restricted to cancer initiation as they are involved in head and neck cancer progression as well. The loss of the TSG function can result from the following independent genetic/molecular events: (i) chromosome aberrations dominated by deletions, then chromatide breaks, (ii) loss of heterozygosity (LOH), (iii) frequent gene mutations and (iv) DNA methylation (usually in a gene promoter region) followed by a lack of gene expression or production of an non-functional gene product. The findings have been applied to establish some diagnostic and prognostic tests. The latter could help in the estimation of the survival period of cancer subjects. There are many attempts to optimize radiotherapy protocols in relation to the TSG structure and function. Studies on gene therapy protocols exploring p53 and p16 genes were also started. Nevertheless, extended knowledge concerning TSG did not produce too many applications so far.